Environmental Manipulations to Minimize Thermal Stress in Laying Hens in a Hot Humid Climate - Ismail, Izzeldin Babiker (2001)
Three experiments were carried out on laying hens (Hisex Brown) to investigate their performances and to determine the adverse effects of high environmental temperature. The hens were housed in light controlled rooms. Temperature treatment experiment (hot and cold), Light treatments experiment (light and dark) and acclimatization to acute heat (38.5) experiment. Rectal temperature, respiration rate, feed intake, egg production, eggshell quality, blood gas and plasma analysis were reported. The effects of high ambient temperature (35°C) and humidity (68.6%) on the physiology and production performance of laying hens showed a significant (p<O.Ol) increase in rectal temperature, respiratory rate, blood pH and efficiency of feed conversion. However the partial pressure of carbon dioxide (PC02), blood bicarbonate (He03-) concentration, feed intake, egg production, egg weight, eggshell thickness and albumen quality were significantly decreased (p<O.O5). Similarly the blood packed cell volume, haemoglobin, sodium, potassium, calcium and phosphorous concentrations were also significantly decreased (p<O.O5). Synchronization of the dark period with the hot period of the day (Ta; 3SoC, RH; 68.6%) to minimize heat stress in laying hens showed significant increases in feed intake and egg production (p<O.Ol), eggshell thickness (p<O.O5), pC02 (p<O.Ol) and blood HC03- concentration (p<O.O5). However, significant decreases in the efficiency of feed conversion (p<O.O5), egg weight (p<O.Ol) and rectal temperature (p<O.O5) were recorded. The blood pH, plasma calcium and phosphorous concentrations of the dark-treated and the light-treated groups were not significantly different. However, plasma cholesterol concentration of the light-treated group was significantly higher (p<O.Ol) than the dark-treated group when exposed to high ambient temperature. The heart was significantly (p<O.O5) heavier and enlarged in the birds kept in the light during the high environmental temperature of 35oC. Acclimatization studies on the dark-treated and light-treated laying hens to acute heat of 38.5°C increases the rectal temperature to 43.9°C and 44.1°C respectively on the first day of acute heat exposure. On the following days the rectal temperature gradually decreased reaching the lowest value on day three for the darktreated and day four for the light-treated group. Similarly, a significant increase in shank and comb temperatures were observed reflecting the body heat load, stimulating vasodilatation in an attempt to cool the body by heat dissipation. The blood pH of the dark-treated and the control groups increased to 7.59 and 7.58, respectively. The pC02 and HC03- concentrations were significantly (P<O.Ol) increased in the dark-treated group. Plasma cholesterol concentration was significantly (p<O.Ol) increased during light and decreased during dark treatments. High temperatures during light or darkness did not affect plasma calcium or phosphorous concentration. The result concluded that the efficiency of feed conversion was improved under heat stress. However, egg production and feed intake were decreased. Dark treatment improved acclimatization to acute heat. Exposure to heat during the light increased plasma cholesterol and heart weight.